Fast Coordinated Power Control for Improving Inertial and Voltage Support Capability of Battery Energy Storage Systems - Zhen Gong; Chengxi Liu; Filipe Faria Da Silva; Yonghao Gui; Claus Leth Bak (CSEE Journal of Power and Energy Systems)
This paper proposes a fast coordinated power control method based on two augmented channels (AC) in battery energy storage system (BESS) to improve inertial and voltage support capability, i.e., a frequency-reactive power channel (FRPC) and a voltage-real power channel (VRPC). For frequency control in the power distribution system with high resistance/inductance ratio, the coupling mechanism between rate of change of frequency (RoCoF) and required reactive power (RRP) of grids is analyzed, indicating RoCoF is proportional to RRP. Thus, RoCoF is utilized in FRPC to generate reactive power for complementary inertial emulating control. Meanwhile, for voltage control, coupling characteristics between rate of change of voltage (RoCoV) and demanding real power (DRP) of grids is also studied, revealing RoCoV is proportional to DRP. Therefore, it can be adopted in VRPC to generate real power for complementary voltage control. Then, grid-voltage-modulated direct power control is selected as the inner power control loop to track power references with faster dynamic performance compared with traditional vector-oriented control. Finally, simulations and hardware-in-loop experiments validate improvement in performance of grid frequency and voltage control based on the proposed method.